Biological characters of Trichogramma dendrolimi (Hymenoptera: Trichogrammatidae) reared in vitro versus in vivo for thirty generations. Issue 1 (December 2017) - Lü, Xin; Han, Shichou; Li, Zhigang; Li, Liying
Abstract Trichogramma dendrolimi which is an economically important biological control agent were reared for 30 generations on a modified artificial medium and natural host. Biological characters were assessed and compared with parasitoids rearedin vivo . Pupation rate and normal adults rate ofin vitro –reared parasitoids were significantly higher compared within vivo –reared parasitoids. The adult emergence rate, number of adults produced, and fecundity ofT. dendrolimi rearedin vitro were lower than those rearedin vivo . The percentage of females and longevity did not vary between the two rearing methods. The overall fitness of the parasitoids reared artificially from the first to the 20th generation was higher than of those reared from the 21st generation onwards. No differences were observed in the fitness parameters of parasitoids rearedin vivo across any of the 30 generations. The results suggest that the modified artificial medium used in this study is suitable for the continuous rearing ofT. dendrolimi for at least 20 generations, and has the potential for the mass production of these parasitoids for use in biological control. Such a substrate could be examined for use in rearing other parasitoid species that are important in biological control.